Formulation optimization and characterization of bamboo/polyvinyl alcohol/clay nanocomposite by response surface methodology - Muhammad, Adamu; Md Rezaur, Rahman; Sinin, Hamdan (Elsevier Ltd., 2019)
An investigation of the effects of montmorillonite nanoclay and polyvinyl alcohol (PVA) treatments on the physical, mechanical, and thermal properties of bamboo reinforced nanocomposites was carried out. Response surface methodology (RSM) was used to develop models for predicting mechanical properties of the nanocomposite and optimized the modification phase change materials. The FTIR spectra of the nanocomposites indicated incorporation of the polymer and nanoclay in the structure and diffractograms from XRD also higher crystallinity of the prepared nanocomposite compared to raw bamboo. The SEM image revealed that of the lumens of the raw bamboo were filled by the polymer and nanoclay after formation of the nanocomposite. Improved mechanical properties were observed in the prepared nanocomposites compared to the raw bamboo with the modulus of elasticity (MOE) increased from 7.82 GPa to 17.32 GPa and modulus of rupture (MOR) increased from 68.67 MPa to 118.74 MPa. Optimal values were found to be 15.082 GPa for MOE and 96.879 MPa for MOR with R2 of 0.9999. Better thermal properties were observed in the developed nanocomposites compared to the raw bamboo as revealed by both the DSC and TGA results.